Assessment of proline function in higher plants under extreme temperatures. (27th February 2023) - Raza, A.; Charagh, S.; Abbas, S.; Hassan, M. U.; Saeed, F.; Haider, S.; Sharif, R.; Anand, A.; Corpas, F. J.; Jin, W.; Varshney, R. K.
Abstract: Climate change and abiotic stress factors are key players in crop losses worldwide. Among which, extreme temperatures (heat and cold) disturb plant growth and development, reduce productivity and, in severe cases, lead to plant death. Plants have developed numerous strategies to mitigate the detrimental impact of temperature stress. Exposure to stress leads to the accumulation of various metabolites, e.g. sugars, sugar alcohols, organic acids and amino acids. Plants accumulate the amino acid 'proline' in response to several abiotic stresses, including temperature stress. Proline abundance may result from de novo synthesis, hydrolysis of proteins, reduced utilization or degradation. Proline also leads to stress tolerance by maintaining the osmotic balance (still controversial), cell turgidity and indirectly modulating metabolism of reactive oxygen species. Furthermore, the crosstalk of proline with other osmoprotectants and signalling molecules, e.g. glycine betaine, abscisic acid, nitric oxide, hydrogen sulfide, soluble sugars, helps to strengthen protective mechanisms in stressful environments. Development of less temperature‐responsive cultivars can be achieved by manipulating the biosynthesis of proline through genetic engineering. This review presents an overview of plant responses to extreme temperatures and an outline of proline metabolism under such temperatures. The exogenous application of proline as a protective molecule under extreme temperatures is also presented. Proline crosstalk and interaction with other molecules is also discussed. Finally, the potential of genetic engineering of proline‐related genes is explained to develop 'temperature‐smart' plants. In short, exogenous application of proline and genetic engineering of proline genes promise ways forward for developing 'temperature‐smart' future crop plants. Abstract : Proline aids in various activities associated with plant growth and development under extreme temperatures, and genetic engineering of proline biosynthesis genes may aid in the design of temperature‐smart future crops.